The AMD-associated genetic polymorphism CFH Y402H confers vulnerability to Hydroquinone-induced stress in iPSC-RPE cells - Armento, Angela; Sonntag, Inga; Almansa-Garcia, Ana-Cristina; Sen, Merve; Bolz, Sylvia; Arango-Gonzalez, Blanca; Kilger, Ellen; Sharma, Ruchi; Bharti, Kapil; Fernandez-Godino, Rosario; de la Cerda, Berta; Clark, Simon J.; et al. (Frontiers in Immunology, 2025)
IntroductionAge-related macular degeneration (AMD), a degenerative disease of the macula, is caused by an interplay of diverse risk factors (genetic predisposition, age and lifestyle habits). One of the main genetic risks includes the Y402H polymorphism in complement Factor H (FH), an inhibitor of complement system activation. There has been, and continues to be, much discussion around the functional consequences of this Y402H polymorphism, whether the soluble FH protein confers its risk association, or if the cells expressing the protein themselves are affected by the genetic alteration. In our study, we examined the cell characteristics of the retinal pigment epithelium (RPE) cells, which play a major role in retinal homeostasis and stability and which are synonymously linked to AMD.MethodsHere, we employ RPE cells derived from induced pluripotent stem cells (iPSC) generated from donors, carrying either homozygous 402Y (low risk) or 402H (high risk) variants of the CFH gene. RPE cells were treated with Hydroquinone (HQ), a component of cigarette smoke, to induce oxidative damage. ResultsIntriguingly, RPE cells carrying high genetic risk proved more vulnerable to oxidative insult when exposed to HQ, as demonstrated by increased cytotoxicity and caspase activation, compared to the low-risk RPE cells. The exposure of RPE cells to RPE conditioned medium, normal human serum (NHS) and inactivated NHS (iNHS) had minimal impact on cell cytotoxicity and caspase activation, nor did the presence of purified soluble FH rescue the observed effects. Considering the known connection of oxidative stress to proteotoxic stress and degrading processes, we investigated the unfolded protein response (UPR) and autophagy. When exposed to HQ, RPE cells showed an increase in autophagy markers; however, iPSC-RPE cells carrying high genetic risk showed an overall reduced autophagic flux. DiscussionOur findings suggest that the degree of cellular susceptibility to oxidative stress is not conferred by soluble FH protein and other complement sources, but intercellularly because of the corresponding genetic risk predisposition. Our data support the hypothesis that RPE cells carrying high genetic risk are less resilient to oxidative stress.